2003
DOI: 10.1002/ijc.11283
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers of lymph node metastasis in oral squamous cell carcinoma by cDNA microarray analysis

Abstract: We surveyed the expression of 557 cancer-related genes in 15 cases of well-differentiated OSCC by cDNA microarray analysis. To identify potential biomarkers for lymph node metastasis, all microarray data were compared by the MannWhitney test and the significance analysis of microarrays between OSCCs with and those without lymph node metastasis. The tissues of OSCCs with lymph node metastasis exhibited increased expression levels of MMP-1, MMP-3, uPA, integrin-␣3, paxillin, tenascin C and IL-6 transcripts. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 37 publications
5
115
0
3
Order By: Relevance
“…In addition, microarray gene expression studies on whole HNSCC tumour samples have identified the overexpression of several MMPs including MMP-2 (Nagata et al, 2003;Chung et al, 2004). Lastly, MMP-2 is among the recently identified predictive genes that show a positive correlation with lymph node metastasis (Roepman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microarray gene expression studies on whole HNSCC tumour samples have identified the overexpression of several MMPs including MMP-2 (Nagata et al, 2003;Chung et al, 2004). Lastly, MMP-2 is among the recently identified predictive genes that show a positive correlation with lymph node metastasis (Roepman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These findings argue for some common alterations, but also obvious differences in the pathogenesis of oesophageal SCC and carcinogenesis of the skin. Altered expression of integrins and MMPs is also a hallmark for other SCCs derived from oral (Mendez et al, 2002;Nagata et al, 2003;Tsai et al, 2004), hypopharyngeal (Cromer et al, 2004), lung (Gogali et al, 2004;Kettunen et al, 2004) and cervical epithelium (Chen et al, 2003). Future confirmation at the protein level and functional analysis of the identified genes in tissue culture Tumour-associated genes in cutaneous SCC development L Hummerich et al and animal model systems will be required to define the individual roles that the identified genes play in tumour initiation, promotion and progression.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] Although most studies evaluate MMP mRNA or immunohistochemical reactivity, which may not correspond to in vivo enzymatic activity, increased active MMP-2 and MMP-9 has prognostic importance in laryngeal SCC 48,49 and oral cavity SCC. 13,50-52 Although MT1-MMP can degrade type I collagen and other matrix components, 29 MT1-MMP also activates MMP-2 and is, therefore, considered a critical enzyme controlling proteolytic activity.…”
Section: Assessment Of Matrix Metalloproteases In Head and Neck Cancermentioning
confidence: 99%